QUANTIFICATION OF GROWTH OF KANGKONG BANGKOK (IPOMEA AQUATICA FORSK.) ON HORIZONTAL AND VERTICAL NUTRIENT FILM TECHNIQUE (NFT) HYDROPONICS SYSTEMS - Kopriadi, Novan
Kale (Ipomea aquatica F.) is a popular food crop and the most widely consumed vegetable commodity in Indonesia, which is 11.30 grams per capita per day. Therefore, many farmers cultivate kale with hydroponic system, one of the most popular systems is the Nutrient Film System (NFT) method. However, lack of experience and knowledge causes crop failure. Therefore, this study aims to quantify the growth of kale (Ipomea aquatica Forsk), determine the productivity of kale in the horizontal and vertical Nutrient Film System (NFT) hydroponic system, and determine the efficiency of absorption of nutrients N, P and K as well as Water Used Efficiency (WUE). ). The research was conducted on 14 February – 24 May 2021 at the start-up Keboen Bapak located in Mekar Jaya Cinanggela, Babakan, Ciparay District, Bandung, West Java at an altitude of 811 meters above sea level. This research uses descriptive analytical method, namely measuring, observing, calculating and analyzing quantitative data on growth, mass balance, and WUE during cultivation in vertical and horizontal NFT hydroponics systems. Based on the results of the study, the results of quantification of kale growth on vertical and horizontal NFT in 'Keboen Bapak' were plant height growth rate of 2.25 cm/day: 2.25 cm/day, stem length rate of 1.83 cm/day. : 1.95 cm/day, root length rate 0.42 cm/day: 0.29 cm/day, leaf area rate 27.11 cm2/day: 20.45 cm2/day and leaf number rate 2.15 strands/day. day: 2.05 pieces/day. The productivity of vertical NFT is 63.90 tons/ha and horizontal NFT is 24.18 tons/ha. This shows that vertical NFT has better growth results than horizontal NFT. The efficient absorption of nitrogen (N), phosphorus (P) and potassium (K) available in the nutrient solution and absorbed by water spinach plants is N 83.97%; P 88.00% ; K 32.05%. Furthermore, the results of water use efficiency (WUE) were obtained at 24.78 kg/m3, so it can be concluded that nutrient absorption and water use are not efficient.